Education as a Political Act: Community-based Participatory Research with Union Women - Cindy Hanson (Adult Education Research Conference, 2012)
The Prairie School for Union Women (PSUW), now celebrating its fifteenth year of operation, is unique in its popular education approach while remaining the only labour school in Canada specifically for women. During the annual school, held in a retreat-like setting in Saskatchewan, groups of 60-160 women engage in a non-formal education experience that emphasizes adult learning principles of facilitation and mentoring, and support for activist practices. The embodiment and development of feminist popular education2 curricula and methodologies in the School‘s operation is central to this experience. The study, Innovations, Opportunities and Challenges: The Story of the Prairie School for Union Women for which I was a researcher working closely with the School‘s Steering Committee, is the first empirical study to explore how well the goals of the school ―to develop women‘s personal and leadership skills, to build solidarity among women workers, and to increase knowledge about the labour movement‖ are being met.